Enhancing engagement with DataCamp Classrooms: transforming online learning experiences - Ismail, Amelia Ritahani (KICT IIUM, 2024)
DataCamp Classroom is a free online learning platform provided by DataCamp for educators and their students. It offers interactive courses and resources focused on machine learning, and programming languages like Python, R, SQL, and more. With DataCamp Classroom, educators can create virtual classrooms, assign courses, track student progress, and access various teaching tools. DataCamp Classrooms improve student engagement in online learning by offering interactive content and hands-on coding exercises. Focusing on real-world applications, particularly in machine learning, students develop essential skills through personalized learning paths. These features foster active participation and enhance learning outcomes, empowering students to excel in areas like data analysis and machine learning within a dynamic digital classroom environment